Nefertiti: A Symbol Of Beauty, Personality, And Political Power - Primov Mukhiddinjon Omonovich; Beknazarova Dilnora Shuxrat qizi; Valiyeva Gulirano Bahromjon qizi (Peerian Journals Publishing, 2025)
This article explores the life, personality, and historical legacy of the ancient Egyptian queen Nefertiti, who lived in the 14th century BC. The article analyzes her emergence as a symbol of beauty, her role alongside Pharaoh Amenhotep IV in political and religious reforms, her palace life, and her reign. It also discusses Nefertiti's mysterious death and the findings uncovered through archaeological research. Special attention is given to the historical events surrounding the Queen's bust, theories about her tomb, and scholarly debates. This article contributes to a deeper understanding of ancient Egyptian history, examining the historical figure of Nefertiti and analyzing the legends and scientific evidence associated with her
Keywords: Nefertiti; Ancient Egypt; Akhenaten; Tutankhamun